Neostagonosporella bambusicola sp. nov. (Phaeosphaeriaceae, Pleosporales) from bamboo in China - Dissanayake, Lakmali S.; Marasinghe, Diana S.; Thambugala, Kasun M.; Kang, Ji-Chuan (Phytotaxa, 2022)
A bitunicate ascomycete was collected on dead bamboo leaves from Guizhou Province, China. Phylogenetic analyses based on large subunit rRNA (LSU), small subunit rRNA (SSU), translation elongation factor 1-α (tef 1-α) and internal transcribed spacers (ITS) revealed that this species belongs to the genus Neostagonosporella (Phaeosphaeriaceae, Pleosporales) and forms a well-supported lineage (98% ML, 1.00BYPP) with N. sichuanensis. This taxon resembles the type species of Neostagonosporella, N. sichuanensis by its globose to subglobose central ostiolate ascomata, cylindrical to cylindric-clavate, short pedicellate asci and hyaline, cylindrical to fusiform ascospores, as well as a close phylogenetic affinity. However, it differs from N. sichuanensis by its comparatively smaller ascomata, cellular, septate pseudoparaphyses and ascospores with thick sheath, whereas N. sichuanensis has comparatively large ascomata, trabeculate pseudoparaphyses and ascospores with comparatively thin sheath. Therefore, we introduce this taxon as a novel species, namely Neostagonosporella bambusicola and compare it with the other species of Neostagonosporella.